2004
DOI: 10.1897/03-184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dissolved organic matter source on acute copper toxicity to Daphnia magna

Abstract: The protective effect of dissolved organic matter (DOM) on metal toxicity to aquatic organisms has been reported by numerous authors. Bioavailability models such as the biotic ligand model (BLM) thus account for this factor to predict metal toxicity to aquatic organisms. Until now, however, few attempts have been made to assess the effect of the DOM source on metal speciation and toxicity and, accordingly, on BLM predictions. The aims of this study were to investigate to what extent DOMs differ in their abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
111
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 32 publications
18
111
2
1
Order By: Relevance
“…Copper is one of the metals that are of particular concern in relation to water quality, because although an essential element, elevated concentrations in the aquatic environment may result in toxicological effects (de Oliveira-Filho et al, 2004;de Schamphelaere et al, 2004). Copper has been classified under the Water Framework Directive as a potential main pollutant (Annex VIII) for which an environmental quality standard (EQS), if required, should be established at the national level (European Commission, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Copper is one of the metals that are of particular concern in relation to water quality, because although an essential element, elevated concentrations in the aquatic environment may result in toxicological effects (de Oliveira-Filho et al, 2004;de Schamphelaere et al, 2004). Copper has been classified under the Water Framework Directive as a potential main pollutant (Annex VIII) for which an environmental quality standard (EQS), if required, should be established at the national level (European Commission, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Dissolved organic carbon (DOC) was quantified using a TOC-V CPN total organic carbon analyser (Shimadzu, UK). A number of studies [21][22] have demonstrated that Specific UltraViolet Absorbance (SUVA) characteristics may provide a relatively straight-forward method for assessing the content of aromatic substances (e.g. carboxylates) in organic matter that have traditionally been considered to represent the substance category that is most significant with regard to ion binding.…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…carboxylates) in organic matter that have traditionally been considered to represent the substance category that is most significant with regard to ion binding. Indeed, SUVA has been proposed as an alternative to DOC as a BLM input [22]. SUVA was determined for all samples at 350 nm in 1 cm quartz cell using a UV-VIS 200 spectrophotometer (Perkin Elmer, UK).…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…Additions of DOC have also been shown to reduce Cu toxicity in a number of aquatic species. In cladocerans, Giesy et al [20] reported that the presence of organic matter reduced the accumulation of Cu in Simocephalus serrulatus, and De Schamphelaere and Janssen [21], as well as De Schamphelaere et al [22] demonstrated the protective effect of natural DOC additions on the copper toxicity in Daphnia magna. Similarly, in fish (rainbow trout [24]; fathead minnow [18]) acute Cu toxicity has been shown to decrease when the concentration of DOC in the exposure water was increased.…”
Section: Effect Of Added Doc On Copper Toxicitymentioning
confidence: 99%